The use of ASH-15 flowstone as a matrix-matched reference material for laser-ablation U − Pb geochronology of calcite - P. Nuriel; J.-F. Wotzlaw; M. Ovtcharova; A. Vaks; C. Stremtan; M. Šala; N. M. W. Roberts; A. R. C. Kylander-Clark (Geochronology, 2021)
Latest advances in laser ablation inductively coupled plasma mass spectrometer (LA-ICPMS) allow for accurate in situ U−Pb dating of carbonate material, with final age uncertainties usually >3 % 2σ. Cross-laboratory reference materials (RMs) used for sample-bracketing are currently limited to WC1 calcite with an age of 254.4±6.5 (2σ). The minimum uncertainty on any age determination with the LA-ICPMS method is therefore ≥2.5 %, and validation by secondary RMs is usually performed on in-house standards. This contribution presents a new reference material, ASH-15, a flowstone that is dated here by isotope dilution (ID) thermal ionization mass spectrometry (TIMS) analysis using 37 sub-samples, 1–7 mg each. Age results presented here are slightly younger compared to previous ID isotope ratio mass spectrometry (IRMS) U−Pb dates of ASH-15 but within uncertainties and in agreement with in situ analyses using WC1 as the primary RM. We provide new correction parameters to be used as primary or secondary standardization. The suggested 238U∕206Pb apparent age, not corrected for disequilibrium and without common-lead anchoring, is 2.965±0.011 Ma (uncertainties are 95 % confidence intervals). The new results could improve the propagated uncertainties on the final age with a minimal value of 0.4 %, which is approaching the uncertainty of typical ID analysis on higher-U materials such as zircon. We show that although LA-ICPMS spot analyses of ASH-15 exhibit significant scatter in their isotopic ratios, the down-hole fractionation of ASH-15 is similar to that of other reference materials. This high-U (≈1 ppm) and low-Pb (<0.01 ppm) calcite is most appropriate as a reference material for other speleothem-type carbonates but requires more-sensitive ICP-MS instruments such as the new generation of single-collector and multi-collector ICP-MS. Reference materials with high-Pb and low-U or both low-U and low-Pb compositions are still needed to fully cover the compositional range of carbonate material but may introduce analytical challenges.